Population projection of Southeast Asia with a time-delay logistic model - Akber, M. Showkat; Hasan, M. Munna; Kabir, M. Humayun; Gani, M. Osman (Fırat Evirgen, 2025)
The rise in population is a vital problem in Southeast Asian countries. It has an immediate and long-term impact on basic human needs such as housing, food, clothes, and medical care. Population forecasting can be crucial to deciding which socioeconomic and population development initiatives should be implemented in a country. The unpredictable increase in population has several drawbacks. This study compares the accuracy of the process and the proximity of two mathematical models: the time-delay (i.e., maturation time) logistic population model and the classical logistic population model. The resources and ecosystems of Bangladesh, Pakistan, India, Nepal, Bhutan, and Afghanistan are under threat due to the increase in human population, as the population of these countries has increased sharply. Hence, countries should solve this problem creatively and efficiently. We determine and compare the population forecasting of the countries using the logistic population model and the time delay population model under different ecological circumstances. The classical logistic and time-delay logistic population model predicts a future population of the countries in Southeast Asia, where the present and past population projections have quite significant agreement with the existing dataset.
Keywords: Computational Ecology and Phylogenetics; Hesaplamalı Ekoloji ve Filogenetik; Ecological Applications (Other); Ekolojik Uygulamalar (Diğer); Biological Mathematics; Biyolojik Matematik